Azman advertising inventory system / Mohd Lutfli Azim Dagang - Dagang, Mohd Lutfli Azim (2012)
Azman Advertising provides a few services such as picture frame, t-shirt printing, stamp embroidered, billboard, signboard, banner (PVC) and buntings. Azman Advertising never used a system for the activities done inside its company. The Inventory system created is to help all the staffs in Azman Advertising to organize all the transaction made for the product used in order to complete all the orders. The methodology used in order to finish this project is the waterfall model. Waterfall model consists of 5 phases consist of requirement, design, implementation, verification and documentation. The Inventory system has 2 levels of user, staff and administrator. The system will allow users to register staff, register product, register supplier, update product quantity, delete product, and other actions. This system will also show the product that is at re-stock level to inform staffs to order the stock again to make sure there is no shortage of product. As a conclusion, the stand alone system created helps Azman Advertising to organize the inventory system of the company. By implementing the inventory system, it will improve the company performance.